Evaluating the Potential of Large-Scale Photovoltaic Power Generation for Rural Electrification in Makurdi Town, Benue State - Nyam, George Gala; Umar, Medina; Iortim, Dennis Mkur; Davuo, Habila Daze (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
The Angstrom-Prescott equation was developed in this research work for Makurdi town over five years from 2012 to 2016 as H/ Ho = 0.126 + 0.644(n/N) using Matlab software R2020 for the prediction of global solar radiation incident on the horizontal surface of Makurdi town and other areas with similar geographical weather conditions. The maximum average amount of global solar radiation over Makurdi town was obtained as 20 MJm-2 day-1 during the dry season and the minimum value of 13 MJm-2 day-1 during the rainy season which is in agreement with the global annual solar radiation range of 25.2 MJm-2 day-1 in the far northern part of Nigeria and 12.6 MJm-2 day-1 in the coastal region respectively. The regression constants for the developed Angstrom-Prescott equation in this work (a=0.126 and b=0.644) showed a significant increment compared with previous work due to the massive use of fossil fuel in Makurdi town which amounted to a high level of global warming in this area. The results obtained were statistically tested with the value of coefficient of determination R2 as 0.669 (66.9%) and that of RMSE as 0.154% showing the high standard level of correlation of the data used and low percentage error of our methods and equation used in this research work. The high values of "a" and "b" (high global solar radiation and high sunshine hours) obtained in this work show great potential for large-scale photovoltaic power generation for rural electrification in Makurdi town and other areas with similar weather conditions for mitigation of global warming effects